2011
DOI: 10.1021/ar2000925
|View full text |Cite
|
Sign up to set email alerts
|

Collapse and Recovery of Green Fluorescent Protein Chromophore Emission through Topological Effects

Abstract: Housed within the 11-stranded β-barrel of the green fluorescent protein (GFP) is the arylideneimidazolidinone (AMI) chromophore, the component responsible for fluorescence. This class of small-molecule chromophore has drawn significant attention for its remarkable photophysical and photochemical properties, both within the intact protein and after its denaturation. All of the proteins so far isolated that have visible light fluorescence have been found to contain an AMI chromophore. These proteins comprise an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 72 publications
3
123
0
Order By: Relevance
“…44,60,72 Both these dyes and GFP chromophores display a common binding-dependent fluorescence enhancement associated with the suppression of a common double-bond photoisomerization chemistry in the excited state. [4][5][6][7][73][74][75] Our ongoing work shows that this analogy can also be applied to electronic structure along the photoisomerization coordinates of some of the dyes studied here. It does seem to us now that there is a general physics underlying the excited state behavior in all of these systems, and an opportunity for the development and application of quite general model Hamiltonians for fluorogenic monomethine dyes.…”
Section: A General Discussionmentioning
confidence: 99%
“…44,60,72 Both these dyes and GFP chromophores display a common binding-dependent fluorescence enhancement associated with the suppression of a common double-bond photoisomerization chemistry in the excited state. [4][5][6][7][73][74][75] Our ongoing work shows that this analogy can also be applied to electronic structure along the photoisomerization coordinates of some of the dyes studied here. It does seem to us now that there is a general physics underlying the excited state behavior in all of these systems, and an opportunity for the development and application of quite general model Hamiltonians for fluorogenic monomethine dyes.…”
Section: A General Discussionmentioning
confidence: 99%
“…Synthetic analogues of the FP chromophore have been extensively used for studying the effect of the chromophore environment on fluorescence emission [42,43]. one typical synthetic analogue is 4ʹ-hydroxybenzilidene-2,3-dimethylimidazolinone (hBdi; Fig.…”
Section: Chromophore Environment and Fluorescence Emissionmentioning
confidence: 99%
“…The fluorescence of hdBi appears when the temperature is below the glass transition temperature of the solvent [44,46,48]. although there is still debate about the mechanism associated with this fast internal conversion, the current consensus attributes it to flexibility or rotation along one of the bonds adjacent to the methylene bridge [42,43]. The chromophore environment in FPs has evolved to prevent this internal conversion from occurring and thus lead to high fluorescence quantum yields.…”
Section: Chromophore Environment and Fluorescence Emissionmentioning
confidence: 99%
“…30−32 Therefore, the vast majority of chemically synthesized HBI-based analogs are exponentially (10 −4 ) less emissive in solution compared to GFP and its mutants. 31 Thus, to maintain emission of HBIbased chromophores, the β-barrel-chromophore interactions present in natural proteins must be replicated to restrict possible nonradiative decay pathways. Recent studies indicated the possibility to suppress the low-energy vibrational modes of HBI-based chromophores through their chemical modification.…”
Section: Introduction and Scopementioning
confidence: 99%